2017
DOI: 10.1098/rstb.2016.0208
|View full text |Cite
|
Sign up to set email alerts
|

Membrane pores: from structure and assembly, to medicine and technology

Abstract: One contribution of 17 to a discussion meeting issue 'Membrane pores: from structure and assembly, to medicine and technology'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Some of these interactions have developed over time as a result of an evolutionary co-existence and adaptation [82]. Bacterial proteins, from symbiotic or pathogenic bacteria, interact with cell receptors of host cells, create pores in the membranes, modify the host cell environment (i.e., toxins), affect cell longevity, and stimulate different cell pathways during infection, among other functions [83,84,85,86,87,88]. They can cause an extensive rewiring of the host cell signaling network, creating a high impact on its health.…”
Section: Targeting Non-essential Processes: the Key To Overcome Rementioning
confidence: 99%
“…Some of these interactions have developed over time as a result of an evolutionary co-existence and adaptation [82]. Bacterial proteins, from symbiotic or pathogenic bacteria, interact with cell receptors of host cells, create pores in the membranes, modify the host cell environment (i.e., toxins), affect cell longevity, and stimulate different cell pathways during infection, among other functions [83,84,85,86,87,88]. They can cause an extensive rewiring of the host cell signaling network, creating a high impact on its health.…”
Section: Targeting Non-essential Processes: the Key To Overcome Rementioning
confidence: 99%
“…This could also lead to the development of more effective therapeutics against bacteria that produce membrane attacking PFTs. 7 Previously, we have shown that pPorA self-assembled as an octamer in the SDS PAGE and gel extracted octamer readily inserted into planar lipid bilayers and formed stable cation-selective pores. 33,34,48 In contrast to pPorA, the pPorU peptides run on an SDS-PAGE gel formed only monomers, indicating the absence of self-assembled stable oligomers.…”
Section: Discussionmentioning
confidence: 93%
“…In nature, various nanometer-sized pores act as ion channels, porins, aquaporins, pore-forming toxins (PFTs), and viral pores. Most often, however, nanopore technology applications employ PFTs involved in immune or infection mechanisms [28]. One of the major advantages is that PFTs are expressed as soluble monomers; oligomerization and pore formation occur spontaneously upon contact with the membrane of the host [29][30][31].…”
Section: Introductionmentioning
confidence: 99%